Navigating Changes: Indonesia’s Bilateral Climate Partnerships and Institutional Reforms Under Changing Leadership - Paramitha, Gracia; Kusumawardhana, Indra (Jurnal Hubungan Internasional, 2025)
This study analyzed the relationship between institutional reforms and climate change partnerships in Indonesia from 2009 to 2021, a period marked by a leadership transition from President Susilo Bambang Yudhoyono to Joko Widodo. It primarily focused on Indonesia’s bilateral climate partnerships, particularly in addressing deforestation challenges. Using the “transformative 4Is+3” framework, this research delved into the dynamics of institutional reforms within Indonesia’s bilateral climate partnerships. The framework integrates leadership transitions, policy experiments, and decentralization issues, expanding the “4Is” paradigm. Through a qualitative method, including interviews and document analysis, this study explored Indonesia’s strategic partnerships with Australia, the United Kingdom, and Norway from 2009 to 2021. The findings illustrated how the complex interplay of institutions, interests, ideas, and information shaped climate policies and partnerships. The results provided an in-depth understanding of the impacts of institutional reforms and leadership changes on the effectiveness of climate cooperation, offering valuable insights for policymakers, academics, and international stakeholders in addressing global climate challenges.